Sialylation of anti‐histone immunoglobulin G autoantibodies determines their capabilities to participate in the clearance of late apoptotic cells. (27th January 2016) - Magorivska, I.; Muñoz, L. E.; Janko, C.; Dumych, T.; Rech, J.; Schett, G.; Nimmerjahn, F.; Bilyy, R.; Herrmann, M.
Summary: The Fc portion of immunoglobulin (Ig)G harbours a single glycosylation site. Glycan sialylation is critical for structure and for certain effector functions of IgG. Anti‐histone IgG of patients with systemic lupus erythematosus is reportedly responsible for the recruitment of polymorphonuclear cells (PMN) to the clearance of apoptotic cells. Autoantibodies decorating secondary necrotic cells (SNEC) induce proinflammatory responses after activation of blood‐borne phagocytes. Analysing the sialylation status of affinity‐purified anti‐histone IgG in patients with systemic lupus erythematosus (SLE), we demonstrated that the anti‐histone IgG was contained preferentially in the non‐sialylated fraction. In functional ex‐vivo phagocytosis studies, non‐sialylated anti‐SNEC IgG directed SNEC preferentially into PMN but did not change their cytokine secretion profiles. In contrast, sialylated IgG reduced the phagocytosis by monocytes of SNEC. Moreover, the sialylated anti‐SNEC IgG was not simply anti‐inflammatory, but switched the cytokine secretion profiles from interleukin (IL)‐6/IL‐8 to tumour necrosis factor (TNF)‐α/IL‐1β. Here we describe how different sialylation statuses of IgG autoantibodies contribute to the complex inflammatory network that regulates chronic inflammation.